Determination of optimum dyeing recipe with different amount of mordants in handmade cotton fabrics woven with olive leaves by grey relational analysis method - GÜNGÖR, FERHAT; ÖZOMAY, MERAL; ÖZOMAY, ZAFER (TAYLOR & FRANCIS LTD, 2022)
While the coloring of textiles was done with natural dyes in history, today it has been completely replaced by chemical dyes and our cultural values have begun to be abandoned. For this reason, various studies are carried out in order to revitalize natural dyeing and to increase its preference. Turkey's flora is rich in terms of plant diversity, thus it makes it easier to facilitate studies related to natural dyeing. We can count the olive tree that has an important place in this diversity and it grows in many regions of our country. In this research, the usability of the natural dye obtained from the leaves of the olive tree, which is very widespread in the world, in cotton fabrics woven with handmade yarns was investigated. In this study, Eflani fabric, woven from 100% cotton yarn with olive leaves, was dyed with a total of 3 different mordant materials of 5 different concentrations. The light and wash fastnesses of the dyed samples were made and the color differences and color efficiencies were calculated and compared using the CIE L * a * b color space system. Grey Relational Analysis (GRA) Method was used for the optimization of dyeing parameters. GRA, which is one of the multi-criteria decision making methods, is an effective method that can be used in situations where there are more or less information and multiple criteria and decision making are complex. There are a total of 9 criteria to decide on the best dyeing together with the fading and staining process obtained from washing damage and with the fading value obtained from lightfastness and color yield. Thanks to the GRA method applied, the evaluation made according to 9 criteria gives us the optimum result. In this experimental study, the effects of 3 different mordant substances and mixtures used in dyeing cotton fabric with olive leaves on color difference and color efficiency were investigated, and it showed that the dyeing with citric acid mordant and using 10% mordant, which is the highest concentration, gave the best fastness values.
Keywords: Grey relational analysis; Karabü k Eflani Fabric; natural dyeing; olive leaf; cotton